MSH6 gene pathogenic variant identified in familial pancreatic cancer in the absence of colon cancer. Issue 3 (March 2020) - Mannucci, Alessandro; Zuppardo, Raffaella A.; Crippa, Stefano; Carrera, Paola; Patricelli, Maria G.; Russo Raucci, Annalisa; Calabrese, Federica; Lazarevic, Dejan; Giannese, Francesca; Tonon, Giovanni; Ferrari, Maurizio; Testoni, Pier A.; et al.
Abstract : Objectives: Lynch syndrome is characterized by pathogenetic variants in the mismatch repair genes and autosomal dominant inheritance with incomplete penetrance. Lynch syndrome is characterized by colorectal and, with lesser and variable extent, extracolonic cancers. We describe a family with MSH6 -dependent Lynch syndrome and familial pancreatic cancer and other tumours (gastric and endometrial), in the absence of colorectal neoplasia. Methods: Patients were analysed by sequencing, Next Generation or Sanger, to identify germinal pathogenic variants in hereditary cancer genes. Results: We identified the MSH6 gene pathogenic variant c.2194C>T, p.(Arg732Ter) in a family with hereditary pancreatic cancer without diagnosed cases of colorectal adenocarcinoma. Seven family members were affected by the MSH6 pathogenic variant. Three had pancreatic adenocarcinoma at 65, 57 and 44 years; one had endometrial cancer at 36 years. None of the remaining three subjects (75, 45 and 17 years old) had developed any cancer yet. Conclusions: Lynch syndrome should be suspected in families with familial pancreatic cancer, even in the absence of colon cancers. Specifically, our observation supports the association between the MSH6 c.2194C>T pathogenic variant and extracolonic tumours and it suggests that MSH6 pathogenic variants are associated with familial pancreatic cancer more frequently than assumed.